Clinico-demographic Characteristics of Coronary Artery Bypass Surgery Patients: Experience of 60 Cases at Referral Cardiac Surgery Hospital in Bangladesh (Journal of Science Foundation, 2017)
Background: Coronary artery bypass surgery is needed in different group of patients.Objective: This study was undertaken to see the different socio-demographic characteristics of patients undergone coronary artery bypass surgery.Methodology: This cross-sectional study was conducted in the Department of Cardiac Surgery at National Institute of Cardiovascular Diseases (NICVD), Dhaka, Bangladesh during January 2014 to December 2015 for a period of two (2) years. Patients undergone CABG after fulfilling the inclusion and exclusion criteria was recruited for this study. The details socio-demographic characteristics of the study population were recorded.Result: A total number of 60 patients were recruited for this study after fulfilling the inclusion and exclusion criteria. The age of the patients undergoing OPCAB surgery ranges from 37 years to 70 years. But most of the patients were in the range of 41 to 60 years which was 50(83.3%). There was an overall male dominance among the patients which was 91.67%. the ratio of male and female was 11.0:1. NYHA class I was in 32(53.3%) cases and class II was 28(46.47%) cases. Hypertension was present in 37(63.3%) cases. Diabetes mellitus and dyslipidemia were present in 50(83.3%) cases and 37(61.7%) cases respectively. Obesity was present in 40(66.7%) cases. Smoking habit was present in 34(56.7%) cases.Conclusion: In conclusion the efficacy of topical tranexamic acid is helpful for reducing postoperative bleeding after OPCAB surgery. Journal of Science Foundation, 2016;14(2):62-65